Physiological Concentrations of Acute-Phase Proteins and Immunoglobulins in Equine Synovial Fluid - Basile, Roberta C. [UNESP]; Ferraz, Guilherme C. [UNESP]; Carvalho, Marsel P. [UNESP]; Albernaz, Raquel M. [UNESP]; Araújo, Renatha A. [UNESP]; Fagliari, José J. [UNESP]; Queiroz-Neto, Antonio [UNESP] (Elsevier, 2013)
Synovial fluid (SF) is capable of reflecting infectious, immunological, or inflammatory joint conditions in horses by altering its composition and appearance. Although plasma and SF compositions are quantitatively different, this latter compartment reflects changes in plasma macromolecules. Therefore, changes in serum immunoglobulin protein concentrations tend also to alter intracapsular levels. Therefore, it is necessary to know the physiological concentrations of proteins present in SF. The aim of this study was to determine the levels of total protein, albumin, transferrin, haptoglobin, α1-acid glycoprotein, ceruloplasmin, and immunoglobulins A and G in SF of six healthy horses. The synovial proteinogram was obtained by sodium dodecyl sulfate polyacrylamide gel electrophoresis. The SF proteins reached a maximum of 25% of serum concentrations, varying inversely with molecular weight of the protein, except for the ceruloplasmin. © 2013 Elsevier Inc.
Keywords: Electrophoresis; Horse; Joint; Proteinogram; SDS-polyacrylamide gel electrophoresis; Equidae